Vegetative Growth Response of Robusta Coffee Seedlings (Coffea canephora Pierre ex A. Froehner) to Various Concentrations of Atonic Growth Regulators - Novi Yulanda Sari; Nursamsi; Muhammad Syahfitra; Novfirman; Dyah Puspita Sari (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Seedling quality is a critical determinant of the long-term productivity of robusta coffee. Under nursery conditions, seedlings often exhibit slow and uneven growth, which may limit canopy development and photosynthetic efficiency. Therefore, strategies that enhance physiological processes are needed to improve seedling performance. Atonik, a plant growth regulator (PGR) containing nitrophenolate compounds, has been reported to stimulate metabolic activity and enhance plant growth. However, information regarding the optimal concentration of Atonik for seed-propagated robusta coffee seedlings remains limited. This study aimed to evaluate the vegetative growth response of robusta coffee seedlings to different concentrations of Atonik and to determine the most effective rate during the nursery stage. The experiment was arranged in a completely randomized design (CRD) with a single factor consisting of five Atonik concentrations (0, 10, 15, 20, and 25 ml/L) and three replications. Observed variables included plant height, leaf number, stem diameter, leaf length, leaf width, total fresh weight, and total dry weight. Data were analyzed using ANOVA followed by Duncan’s Multiple Range Test at 5%. The results showed that Atonik application significantly increased plant height, stem diameter, leaf width, total fresh weight, and total dry weight. The 15 ml/L concentration significantly increased plant height and leaf width, whereas the 20 ml/L concentration significantly improved stem diameter and biomass accumulation. Overall, the 20 ml/L treatment was the most effective in enhancing seedling vigor during the nursery stage.